Anti-alcohol campaign in the Soviet Belarus in the second half of the 1980s - Huzhalouski, Alexander A. (Journal of the Belarusian State University. History, 2025)
The article examines the campaign against drunkenness and alcoholism in the second half of the 1980s in the Soviet Belarus. It notes that alcohol consumption was a serious problem for Belarusian society and was harmful to public health. Legislative initiatives and practical actions taken by the party and the government to restrict moonshining and the state circulation of alcohol are examined. The activities of the Belarusian Republican Voluntary Society for the Fight for Sobriety, which made efforts to combat drunkenness and promote a sober lifestyle, are analysed. It is pointed out that the state’s anti-alcohol policy was contradictory and did not have any significant positive results. The restrictions introduced led to queues in shops, the consumption of alcohol substitutes and an increase in moonshining.